Lyophilized horizontal platelet rich fibrin promotes the healing of infected burns/wounds by modulating macrophage polarization and fibroblast migration - Chai, Jihua; Miao, Detian; Miron, Richard J.; Farshidfar, Nima; Xu, Shuo; Zhang, Xiaoxin; Wang, Yulan; Bai, Yi; Sun, Hualing (Frontiers in Bioengineering and Biotechnology, 2025)
BackgroundThe treatment of infected burns is a major clinical challenge. Platelet-rich fibrin produced via horizontal centrifugation (H-PRF) has been characterized with antimicrobial and tissue regenerative properties. Noteworthy, its lyophilized form (Ly-H-PRF), which can be conveniently preserved, may also have similar regenerative potential for the treatment of infected burns. The aim of this study was to investigate whether Ly-H-PRF could promote wound healing and its regulatory mechanism in various in vitro and in vivo models simulating infected burns/wounds.MethodsVenous blood of healthy volunteers was drawn, horizontally centrifuged at 700 RCF for 8 min, and lyophilized to obtain Ly-H-PRF. Ly-H-PRF was dissolved in culture medium, and its antimicrobial effects were evaluated on Staphylococcus aureus (S.a) and Escherichia coli (E.c) by the poured-plate method. Furthermore, the effects of Ly-H-PRF on the cell cycle and polarization of macrophages after lipopolysaccharide (LPS) stimulation were also investigated by fluorescence staining and flow cytometry. The effects of Ly-H-PRF on skin fibroblasts after LPS culture were also tested by flow cytometry, a transwell assay, and a scratch assay. Lastly, a mouse second-degree burn model was used with four groups, including 1) PBS, 2) S.a infection, 3) S.a infection + burn ointment, and 4) S.a infection + Ly-H-PRF. Histological assessment was used to investigate the healing of the burn wound tissues, inflammatory cell infiltration, neo-collagenous tissues, and macrophage polarization after 5 days.ResultsLy-H-PRF effectively inhibited the growth of S.a and E.c. It also protected macrophages from LPS-stimulated apoptosis and reduced LPS-induced macrophage M1 polarization and promoted M2 polarization. Ly-H-PRF further protected fibroblasts from LPS-stimulated apoptosis and facilitated fibroblasts migration. In the in vivo burn wound model, S.a infections led to a greater wound enlargement and ulceration at 5 days post-op, and routine use of burn ointment was less effective than treatment of infected wounds with Ly-H-PRF. Noteworthy, the Ly-H-PRF promoted wound healing, reduced inflammatory cell infiltration, and increased collagen synthesis.ConclusionThe present study demonstrated that Ly-H-PRF promoted the healing of infected burn wounds by exerting an antibacterial effect, regulating macrophage polarization, and promoting skin fibroblast migration. Our results provide a pre-theoretical basis for the clinical application of Ly-H-PRF as an economical and convenient treatment for infection control and to promote tissue healing in infected burn wounds.